The developing role of fetal magnetic resonance imaging in the diagnosis of congenital cardiac anomalies: A systematic review - Rohit S Loomba; Suraj Chandrasekar; Parinda H Shah; Prateek Sanan (Annals of Pediatric Cardiology, 2011)
Advances in the fetal magnetic resonance imaging (MRI) over the last few years have resulted in the exploring the use of fetal MRI to detect congenital cardiac anomalies. Early detection of congenital cardiac anomalies can help more appropriately manage the infant′s delivery and neonatal management. MRI offers anatomical and functional studies and is a safe adjunct that can help more fully understand a fetus′ cardiac anatomy. It is important for the obstetricians and pediatric cardiologists to be aware of the recent advancements in fetal MRI and it`s potential utility in diagnosing congenital cardiac anomalies.